THE IMPACT OF A MULTIDISCIPLINARY AND MULTIMODAL APPROACH ON SEPSIS OUTCOMES IN A LARGE COMMUNITY HOSPITAL SYSTEM. Issue 12 (18th November 2016) - Penoyer, Daleen; Cheatham, Michael; Inderwiesen, Paula
Abstract : Background: Sepsis is an important contributor to hospital morbidity and mortality, with annual costs estimated $20 billion. Early identification and treatment is key to improving sepsis outcomes. The Surviving Sepsis Campaign recommended sepsis bundles to improve quality with sepsis management. Objectives: Increase recognition of sepsis Provide clinical tools to facilitate sepsis bundle use Decrease sepsis mortality Methods: We upgraded clinical tools based upon new sepsis guidelines, and developed a comprehensive sepsis initiative across an eight hospital system. A multidisciplinary team of key stakeholders across the care continuum at each hospital led multimodal efforts at the corporate, hospital and unit level, addressing opportunities to improve sepsis care across all populations. All clinical caregivers were required to complete sepsis education offered in multiple formats. We held a "kickoff" for eight hospital teams through an interactive and simulation-based Sepsis Superbowl program in 2015. Our informatics team developed novel sepsis care adjuncts: SIRS surveillance with automatic prompts for sepsis assessment, upgraded EMR sepsis screens, compliance reports, revised EMR order set, and interactive physician progress note which fulfills documentation requirements for sepsis core measures. The ED developed a sepsis risk tool for triage and ED and inpatient sepsis alert processes to facilitate timely treatment. Results: Hospital sepsis teams meet regularly, report outcomes data, address barriers, and make clinical sepsis rounds. Compared to 2013, we've had 37% reduction in all sepsis mortality and 32% reduction from severe sepsis/septic shock. Conclusions: Improving sepsis care across a large healthcare system was possible using multidisciplinary and multimodal strategies and resulted in reduced sepsis mortality.Figure 1 Figure 2